2013
DOI: 10.1016/j.neulet.2013.08.069
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of PPAR-gamma in the cerebrospinal fluid of patients with multiple sclerosis

Abstract: Peroxisome proliferator-activated receptor gamma (PPARγ), a ligand-activated transcriptional factor involved in the regulation of glucose and lipid metabolism, has gained interest as a potential therapeutic target in multiple sclerosis (MS) due to its potent immunoregulatory properties and the therapeutic efficacy of its ligands in experimental autoimmune encephalitis (EAE). Elevated expression of PPARγ has been observed in the spinal cord of EAE mice and in an in vitro model of antigen-induced demyelination; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 38 publications
0
16
1
1
Order By: Relevance
“…Analogously, owing to their engagement in the regulation of neuroinflammation and innate immune response, PPAR dysfunction may play a role in the molecular mechanisms that trigger multiple sclerosis (MS) [129,130]. Interestingly, in PBMC of patients affected by MS, PPAR-γ expression was decreased [131,132].…”
Section: Neurological Disordersmentioning
confidence: 99%
“…Analogously, owing to their engagement in the regulation of neuroinflammation and innate immune response, PPAR dysfunction may play a role in the molecular mechanisms that trigger multiple sclerosis (MS) [129,130]. Interestingly, in PBMC of patients affected by MS, PPAR-γ expression was decreased [131,132].…”
Section: Neurological Disordersmentioning
confidence: 99%
“…A recent study demonstrated that a ligand-activated transcription factor known as peroxisome proliferator-activated receptor gamma (PPARγ) playing a pivotal role in regulation of glucose and lipid metabolism is markedly increased in CSF of MS patients ( 27 ). Furthermore, elevated expression of PPARγ has been reported within the spinal cord of EAE mice ( 28 ) and in an in vitro model of antigen induced demyelination ( 29 ).…”
Section: Glucose Metabolism and Multiple Sclerosismentioning
confidence: 99%
“…In this regard, it is interesting that PPAR γ may regulate the expression of β 1 integrin [13]. Moreover, in MS patients free of therapy, a pronounced elevation of PPAR γ levels in the cerebrospinal fluid (CSF) was associated with increased intrathecal inflammation [14]. Overall, these data suggest that PPAR γ -mediated processes may contribute to the mechanism of action of NTZ.…”
Section: Discussionmentioning
confidence: 99%